THE ART OF CREATING AN IDENTITY FROM STORYTELLING USING CARTOONS AS A BASE TO CAMPAIGN TO STOP VIOLENCE AND SEXUAL HARASSMENT AGAINST PEOPLE IN SOCIETY - Promjeen, Wanwisa; Boonchuai, Poschanan (Journal of Social Science and Cultural, 2025)
This research has the purpose of 1) to create knowledge about the dimensions of creative work. The art strategy of creating identity from storytelling using channel cartoons as a base. Which will lead to guidelines for creating awareness for the public about the way to reduce violence and sexual harassment of people in society 2) Seek and study guidelines to prevent violence and sexual harassment users. For the elimination of the above problems to society in various dimensions 3) Develop a Practice Based Research model, creating media to fix and prevent Including sustainable solutions to the country's problems To eliminate all forms of violence and sexual harassment Using the foundation research methodology (Grounded Theory), the tools used in this research are the expert interview form, the interview form of the target group representative, and the awareness evaluation form. The results of the research can be summarized as follows: 1) The opinions of experts on the problem of severity. To the appropriateness of the work, 9 people found that the quality of the appropriateness of the work is at a very high level ( = 3.78) 2) The results of the interview for the target group representatives (Try Out) on the suitability of developing channel cartoon creations, 30 people, found that channel cartoons and symbolic narratives help readers understand the problem of violence and sexual harassment in depth. 3) Assessment of awareness by the target group who witnessed violence through various media, aged 18-29 years old, 352 people by evaluating the awareness of the creation of the channel cartoon. There is a learning awareness at the highest level ( = 4.90) It is considered a creative approach to promote a safer and more equal society.